Two new species of Saetherolabis Andersen et Mendes, 2007 from Brazil (Diptera: Chironomidae, Orthocladiinae) - Andersen, Trond; Mendes, Humberto F.; Pinho, Luiz C. (Zootaxa, 2012)
The genus Saetherolabis Andersen et Mendes, 2007 was described based on S. pectinata Andersen et Mendes, 2007 from theAmazon forest in Brazil. Below two new species of Saetherolabis, S. iperuype sp. n. and S. siriype sp. n., are described and figured based on males from Mata Atlântica in São Paulo and Sergipe States in Southeastern and Northeastern Brazil.